Endometrial cancer: results of clinical and histopathological staging compared to magnetic resonance imaging using an endorectal surface coil - Brocker, Kerstin A.; Alt, Céline D.; Breyer, Ulrike; Hallscheidt, Peter; Sohn, Christof (Archives of gynecology and obstetrics, 2014)
The aim of this study was to evaluate the staging accuracy of magnetic resonance imaging (MRI) with an endorectal surface coil on patients with endometrial cancer compared to results obtained using the International Federation of Gynecology and Obstetrics (FIGO) classification and histopathology.